Influence of exchanged cations (Na+, Cs+, Sr2+ and Ba2+) on xylene permeation through ZSM-5/SS tubular membranes - Tarditi, Ana Maria (2008)
Na-ZSM-5 membranes were synthesized by secondary growth on the outer surface of stainless steel porous tubes. The membranes were ion-exchanged with Cs+, Ba2+ and Sr2+ to investigate their effect upon the separation of p-xylene from m-xylene and o-xylene. The permeation through the membranes was measured between 150 and 400 °C using each xylene isomer separately and a ternary mixture. All the membranes were selective to p-xylene in the temperature range studied. N2 and xylene permeation measurements together with SEM observations were used to determine whether or not cracks and/or pinholes developed after exposure to the xylene isomers at high temperature (400 °C). Neither pore blockage nor extra-zeolitic pores developed after the ion exchange procedure and subsequent calcination. Furthermore, duplicate synthesized membranes of each cation form had similar separation factors and permeances. The duplicate values differ much less than the measurement error. The p-xylene permeation flux decreased in the order: Na-ZSM-5 > Ba-ZSM-5 > Sr-ZSM-5 ≅ Cs-ZSM-5 while the permeation flux of the m- and o-xylene decreased in the order Na-ZSM-5 > Sr-ZSM-5 > Ba-ZSM-5 > Cs-ZSM-5. The membrane that exhibited the best performance was Ba-ZSM-5, with a maximum p/o separation factor of 8.4 and a p-xylene permeance of 0.54 × 10-7 mol s-1 m-2 Pa-1 at 400 °C. © 2007 Elsevier B.V. All rights reserved.